Community-based management of acute malnutrition in Bangladesh: feasibility and constraints - Choudhury, Nuzhat; Ahmed, Tahmeed; Hossain, Md Iqbal; Mandal, Barendra Nath; Mothabbir, Golam; Rahman, Mustafizur; Islam, M Munirul; Husain, Mohammad Mushtuq; Nargis, Makhduma; Rahman, Ekhlasur (© 2014 United Nations University Press, 2017)
This article was published in the Food and Nutrition Bulletin [© 2014 United Nations University Press] and The Journal's website is at: https://www.ncbi.nlm.nih.gov/pubmed/25076775